Composite electrocatalyst as well as preparation method and application thereof

By mixing sulfide or selenide with noble metal solution at room temperature and reacting it with an oxidant, a composite electrocatalyst is prepared, which solves the problems of large overpotential and insufficient durability under high current density, and achieves high performance and long stability.

CN119824454APending Publication Date: 2025-04-15WUHAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510155247.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The sulfide electrocatalyst modified with precious metal nanoparticles prepared by the prior art has a large overpotential and insufficient durability at high current density.

Method used

A composite electrocatalyst was prepared by mixing sulfide or selenide with a noble metal solution and adding an oxidant at room temperature to react. This method accelerates the reaction rate of precious metal ions with sulfides or selenides, and realizes the rapid preparation of high-performance, high-uniformity, noble metal nanoparticles modified sulfide or selenide composite catalysts at room temperature.

Benefits of technology

The prepared catalyst has a smaller mass transfer rate and a smaller internal resistance, has a smaller overpotential at high current density and has a longer stability. It is suitable for applications such as electrolyzing and hydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824454A_ABST
    Figure CN119824454A_ABST
Patent Text Reader

Abstract

The invention discloses a composite electrocatalyst and a preparation method and application thereof. The preparation method of the composite electrocatalyst comprises the following steps: mixing sulfide or selenide with a noble metal solution to obtain a mixture; and mixing the mixture with an oxidizing agent, and reacting to obtain the composite electrocatalyst. The oxidizing agent is added, so that the reaction rate of noble metal ions and sulfide or selenide is accelerated, and the high-performance and high-uniformity sulfide or selenide composite catalyst modified by noble metal nanoparticles is rapidly prepared at room temperature; the technical problems that an existing noble metal nanoparticle supported catalyst is long in preparation time and difficult to apply in an engineering mode are solved. And the prepared composite catalyst has the advantages of low mass transfer rate, low internal resistance, low overpotential under high current density, long stability and wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a composite electrocatalyst and a preparation method and application thereof. Background Art

[0002] With the acceleration of global fossil fuel consumption, rising oil prices and global warming, the world is looking for clean and renewable energy. The hydrogen produced by electrocatalytic water splitting powered by renewable energy is of high purity and cleanliness, and is considered to be one of the most effective ways to solve energy crises and environmental problems around the world. For the hydrogen evolution reaction (HER), the best performing catalyst is the precious metal Pt, but its large-scale application is restricted by its high price and production cost. Therefore, finding efficient, economical and stable electrode catalysts is a decisive means to popularize water electrolysis hydrogen production technology in the market.

[0003] Lamellar transition metal sulfides have a lamellar structure similar to graphene and belong to the hexagonal system. They have the advantages of low price, sufficient raw materials, good corrosion resistance, and good catalytic performance. At present, ruthenium-doped molybdenum sulfide materials have been used for water electrolysis, but they are usually prepared by soaking in high-concentration ruthenium salts and hydrothermal methods, which have no advantages in terms of ruthenium consumption or preparation time. In addition, in terms of performance and stability, molybdenum disulfide modified by this method is usually difficult to be used at 100 mA / cm 2 Long-term operation at high current density.

[0004] Lei Xiaodong and others from Beijing University of Chemical Technology mixed nickel-doped molybdenum sulfide prepared by hydrothermal method with ruthenium chloride solution and stirred it for 3 hours to obtain a molybdenum disulfide catalyst with high performance ruthenium nickel single atom dispersion. The catalyst has a high conductivity at 10 mA / cm 2 The overpotential of water electrolysis to produce hydrogen is only 32 mV, which can be achieved at 10 mA / cm 2 The electrocatalyst was prepared by Zeng Xiaofei and others from Beijing University of Chemical Technology using the ultra-gravity method. The electrocatalyst has a stable operation of 10 mA / cm 2 The overpotential under the condition was only 29 mV, but after 1000 cycles under the condition, the overpotential decayed to 41 mV. This shows that the ultra-gravity method can successfully prepare catalysts modified with nano-precious metal particles, but their combination is unstable and difficult to withstand long-term stability tests, which further shows the limitations of operation under high current density. Summary of the invention

[0005] In order to overcome the above-mentioned defects of the prior art, the purpose of the present invention is to provide a composite electrocatalyst and a preparation method and application thereof, so as to solve the problems of large overpotential and insufficient durability of sulfide electrocatalysts modified with precious metal nanoparticles prepared by the prior art at high current density.

[0006] To achieve the above object, the present invention is implemented through the following technical solutions: In a first aspect, the present invention provides a method for preparing a composite electrocatalyst, comprising the following steps: mixing a sulfide or a selenide with a noble metal solution to obtain a mixture; The mixture is mixed with an oxidant and reacted to obtain a composite electrocatalyst.

[0007] Preferably, the sulfide or selenide has a nanosheet morphology.

[0008] Preferably, the sulfide is one or more of molybdenum sulfide, cobalt sulfide, nickel sulfide, copper sulfide, and iron sulfide; and the selenide is one or more of nickel selenide, indium selenide, and cadmium selenide.

[0009] Preferably, the amount of sulfide or selenide is 1-50 mg; the concentration of the noble metal solution is 0.1×10 -4 ~ 0.1mol / L, the addition amount is 1~10 mL; the concentration of the oxidant is 20~30 wt%, and the addition amount is 1~200 μL.

[0010] Preferably, the noble metal is one or more of ruthenium, platinum, iridium, rhodium and palladium.

[0011] Preferably, the oxidant is one or more of hydrogen peroxide, ozone, and sodium hypochlorite.

[0012] Preferably, the mixture is mixed with the oxidant by mixing the oxidant at a concentration of 0.1×10 -4 was added to the mixture at a rate of ~0.1 mL / min.

[0013] Preferably, the reaction temperature is room temperature and the reaction time is 1 to 20 min.

[0014] Preferably, the preparation method further comprises filtering the reaction product, washing it alternately with ethanol and deionized water, and then drying it to obtain a composite electrocatalyst.

[0015] In a second aspect, the present invention provides a composite electrocatalyst prepared by the preparation method described in the first aspect.

[0016] In a third aspect, the present invention provides an application of the composite electrocatalyst as described in the second aspect in producing hydrogen by electrolysis of water.

[0017] The beneficial effects of the present invention are: The present invention accelerates the reaction rate of noble metal ions with sulfide or selenide by adding an oxidant, thereby realizing rapid preparation of a high-performance and high-uniformity noble metal nanoparticle-modified sulfide or selenide composite catalyst at room temperature, thereby solving the technical problems of long preparation time and difficulty in engineering application of existing noble metal nanoparticle-supported catalysts; and the prepared catalyst has a lower mass transfer rate and a lower internal resistance, a lower overpotential at a high current density, and a longer stability, thus having broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.

[0019] Figure 1 is a SEM image of Ru-MoS2-H2O2 and MoS2 prepared in Example 1; Figure 2 is a TEM image of Ru-MoS2-H2O2 and MoS2 prepared in Example 1; Figure 3 1 is the XRD diagram of the catalyst and MoS2 prepared in Example 1, Comparative Example 1 and Comparative Example 2; Figure 4 It is the EPR test graph of the catalyst and MoS2 prepared in Example 1, Comparative Example 1 and Comparative Example 2; Figure 5 The electrocatalytic performance test results of the catalysts and MoS2 prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown; Figure 6 The electrocatalytic performance test results of the composite electrocatalyst and MoS2 prepared in Example 2 and Comparative Example 1; Figure 7 The electrocatalytic performance test results of copper sulfide modified with different noble metal nanoparticles in Example 3; Figure 8 These are the test results of the electrocatalytic performance of iron sulfide modified with different precious metal nanoparticles in Example 4. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] An embodiment of the present invention provides a method for preparing a composite electrocatalyst, comprising the following steps: (1) Mixing a sulfide or selenide with a noble metal solution to obtain a mixture; wherein the amount of the sulfide or selenide is 1 to 50 mg, and the concentration of the noble metal solution is 0.1×10 -4 ~ 0.1 mol / L, the dosage is 1~10 mL. Precious metals include but are not limited to one or more of ruthenium, platinum, rhodium, iridium, and palladium. Sulfides include but are not limited to one or more of molybdenum sulfide, cobalt sulfide, nickel sulfide, copper sulfide, and iron sulfide; selenides include but are not limited to one or more of nickel selenide, indium selenide, and cadmium selenide.

[0022] (2) Add 20-30 wt% oxidant at 0.1×10 -4 ~0.1 mL / min is added to the mixture, the amount of the oxidant added is 1~200 μL, and the reaction is stirred at room temperature for 1~20 min to obtain a reaction product; wherein the oxidant can be any substance that can show oxidizing properties in a chemical reaction, including but not limited to one or more of hydrogen peroxide, ozone, and sodium hypochlorite.

[0023] (3) The reaction product is filtered, rinsed alternately with ethanol and deionized water, and then dried to obtain a composite electrocatalyst.

[0024] In some preferred embodiments, the sulfide or selenide used in step (1) has a nanosheet morphology, and the composite electrocatalyst prepared by the preparation process provided by the present invention comprises sulfide or selenide nanosheets, and precious metal nanoparticles supported on the surface of the sulfide nanosheets or selenide nanosheets; wherein the sulfide nanosheets have sulfur vacancies and the selenide nanosheets have selenium vacancies.

[0025] In some preferred embodiments, the content of the precious metal element in the composite electrocatalyst prepared by the preparation process provided by the present invention is 0.1-20 wt%.

[0026] In order to make the purpose, technical scheme and advantages of the present invention clearer, the embodiments of the present invention will be further described in detail below. If there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. For example, molybdenum disulfide with a flower-like morphology is prepared by an existing process. If the manufacturer of the reagents or instruments used is not indicated, it is regarded as a conventional product that can be purchased commercially.

[0027] Example 1 A method for preparing a composite electrocatalyst comprises the following steps: (1) Take 6 mg of flower-shaped MoS2 and load it on a graphite felt with an area of ​​0.5×1 cm. Then place it in 5 mL of 1 mmol / L ruthenium chloride solution and stir it evenly to obtain a mixture.

[0028] (2) While stirring, add 200 μL of 30% hydrogen peroxide to the mixture at a rate of 0.075 mL / min. Stir the mixture at room temperature for 5 min to obtain a reaction product.

[0029] (3) The reaction product is filtered, rinsed alternately with ethanol and deionized water, and then dried to obtain a composite electrocatalyst, which is nano-ruthenium-modified molybdenum disulfide, labeled as Ru-MoS2-H2O2.

[0030] Example 2 A method for preparing a composite electrocatalyst is basically the same as that in Example 1, except that the precious metal solutions used in step (1) of this embodiment are rhodium chloride, palladium chloride, iridium chloride, and platinum chloride solutions, respectively, to obtain four types of molybdenum disulfide modified with different precious metal particles, which are labeled as Rh-MoS2-H2O2, Pd-MoS2-H2O2, Ir-MoS2-H2O2, and Pt-MoS2-H2O2, respectively.

[0031] Example 3 A method for preparing a composite electrocatalyst is basically the same as that of Example 1, except that the sulfide used in step (1) of this embodiment is copper sulfide, and the precious metal solutions used are rhodium chloride, palladium chloride, iridium chloride, platinum chloride, and ruthenium chloride solutions, respectively, to obtain five copper sulfides modified with different precious metal nanoparticles, which are labeled as Rh-CuS-H2O2, Pd-CuS-H2O2, Ir-CuS-H2O2, Pt-CuS-H2O2, and Ru-CuS-H2O2, respectively.

[0032] Example 4 A method for preparing a composite electrocatalyst is basically the same as that of Example 1, except that the sulfide used in step (1) of this embodiment is Fe2S3, and the precious metal solutions used are palladium chloride and iridium chloride solutions, respectively, to obtain two kinds of iron sulfides modified with different precious metal nanoparticles, which are marked as Pd-Fe2S3-H2O2 and Ir-Fe2S3-H2O2, respectively.

[0033] Comparative Example 1 This comparative example is basically the same as Example 1, except that deionized water is used in step (1) instead of the ruthenium chloride solution. Specifically, the comparative example comprises the following steps: (1) Take 6 mg of flower-shaped MoS2 and load it on a graphite felt with an area of ​​0.5 × 1 cm. Then place it in 5 mL of deionized water and stir it evenly to obtain a mixture.

[0034] (2) While stirring, add 200 μL of 30% hydrogen peroxide to the mixture at a rate of 0.075 mL / min. Stir the mixture at room temperature for 5 min to obtain a reaction product.

[0035] (3) The reaction product is filtered, rinsed alternately with ethanol and deionized water, and then dried. The resulting electrocatalyst is molybdenum disulfide rich in sulfur vacancy defects, labeled as MoS2-H2O2.

[0036] Comparative Example 2 This comparative example is basically the same as Example 1, except that deionized water is used in place of the hydrogen peroxide solution in step (2). Specifically, the comparative example comprises the following steps: (1) Take 6 mg of flower-shaped MoS2 and load it on a graphite felt with an area of ​​0.5×1 cm. Then place it in 5 mL of 1 mmol / L ruthenium chloride solution and stir it evenly to obtain a mixture.

[0037] (2) While stirring, add 200 μL of deionized water to the mixture at a rate of 0.075 mL / min. Stir the mixture at room temperature for 5 min to obtain a reaction product.

[0038] (3) The reaction product is filtered, rinsed alternately with ethanol and deionized water, and then dried to obtain a composite electrocatalyst, which is nano-ruthenium-modified molybdenum disulfide, labeled as Ru-MoS2.

[0039] Performance Testing 1. Scanning electron microscope and transmission electron microscope test Figure 1 These are scanning electron microscope (SEM) images of Ru-MoS2-H2O2 and MoS2 prepared in Example 1, where a is the SEM image of MoS2 and b is the SEM image of Ru-MoS2-H2O2. It can be seen that before modification, MoS2 is a flower-like structure assembled from flakes, while the morphology of MoS2 does not change after modification with ruthenium nanoparticles, indicating that the present invention will not affect the macroscopic morphology of MoS2 during the Ru nanoparticle modification process.

[0040] Figure 2 These are transmission electron microscope (TEM) images of Ru-MoS2-H2O2 and MoS2 prepared in Example 1, where a is the TEM image of MoS2 and b is the TEM image of Ru-MoS2-H2O2. It can be seen that the surface of the unmodified molybdenum disulfide nanosheets is smooth. Figure 2 b and Figure 2 Compared with a, ruthenium nanoparticles are uniformly dispersed on the surface of MoS2 nanosheets, indicating the successful preparation of the composite electrocatalyst.

[0041] 2. X-ray diffraction test Figure 3 The XRD patterns of the catalysts and MoS2 prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown in Figure 1. The XRD patterns of different samples are used to characterize the crystal phase composition of different samples and the vacancy generation after the reaction under different conditions. Figure 3 It can be seen that compared with MoS2, the peak position of Ru-MoS2 and Ru-MoS2-H2O2 samples at 14.4° did not shift, while the peak position of MoS2-H2O2 shifted to a smaller angle. This is because H2O2 reacted with MoS2 and produced sulfur vacancies, while Ru-MoS2-H2O2 hardly produced more sulfur vacancies due to the presence of H2O2.

[0042] 3. Element content test The content distribution of different elements in the Ru-MoS2-H2O2 sample of Example 1 was measured using a transmission electron microscope. The results are shown in Table 1.

[0043] Table 1 Content distribution of different elements in Ru-MoS2-H2O2

[0044] As can be seen from Table 1, Ru-MoS2-H2O2 contains 18.54 wt% of ruthenium, indicating that the composite electrocatalyst prepared in Example 1 is nano-ruthenium-modified molybdenum disulfide.

[0045] The ICP method was used to test the contents of Mo, S and Ru elements in the solution after different reaction times in the preparation of Ru-MoS2-H2O2 in Example 1. The product of reaction for 1 min was recorded as Ru-MoS2-H2O2-1, the product of reaction for 3 min was recorded as Ru-MoS2-H2O2-3, and the product of reaction for 5 min was recorded as Ru-MoS2-H2O2-5. The test results are shown in Table 2.

[0046] Table 2 Element contents in the solution after reaction under different conditions

[0047] As can be seen from Table 2, during the preparation process of the present invention, the ruthenium content in the solution decreases, indicating that as the reaction time increases, the content of ruthenium nanoparticles in the product continues to increase, indicating that the solution system of noble metals and hydrogen peroxide in the present invention can promote the rapid formation of ruthenium particles on the surface of molybdenum sulfide. It can be seen from the comparison between MoS2-H2O2 and Ru-MoS2-H2O2-5 that after the reaction is completed, the Mo and S content in the former solution is 1.48 times that of the latter, indicating that H2O2 promotes the conversion of ruthenium from ionic state to elemental state in the reaction process of Ru-MoS2-H2O2-5.

[0048] 4. EPR test EPR was used to qualitatively characterize sulfur vacancies and determine the changes in the relative content of sulfur vacancies by peak height. Figure 4 The EPR test diagrams of the catalyst and MoS2 prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown in FIG. Figure 4 a It can be seen that there are a small amount of sulfur vacancies in the MoS2 substrate. The sulfur vacancy content in Ru-MoS2 and MoS2 substrates is close, and MoS2-H2O2 has the most sulfur vacancies. Compared with the MoS2 substrate, Ru-MoS2-H2O2 generates some sulfur vacancies, but the sulfur vacancy content is much smaller than that in MoS2-H2O2. This also further indicates that in the preparation process of Ru-MoS2-H2O2, H2O2 promotes the formation of Ru nanoparticles by regulating the electronic structure of the element, and only a small part reacts with the MoS2 substrate to generate sulfur vacancies. Figure 4 b is the number of sulfur vacancies in Ru-MoS2-H2O2 prepared at different reaction times. It can be seen that the sulfur vacancy contents of the samples (Ru-MoS2-H2O2-1, Ru-MoS2-H2O2-3, Ru-MoS2-H2O2-5) after 1, 3, and 5 min of reaction are similar, indicating that as the reaction time increases, H2O2 will not further react with the MoS2 substrate to generate more sulfur vacancies.

[0049] 5. Electrocatalytic performance test 5.1 Overpotential (electrocatalytic activity) test An electrochemical workstation (Princeton) was used to perform electrochemical tests on the composite electrocatalysts of Examples 1 to 4 and Comparative Examples 1 to 2. Specifically, a three-electrode system was used for the test, wherein the composite electrocatalyst was the working electrode of the three-electrode system, the graphite rod was the counter electrode, and the mercury / mercury oxide electrode was the reference electrode, and the electrochemical properties such as LSV and EIS were measured in a 1.0 M KOH electrolyte solution.

[0050] According to the above linear sweep voltammetric curves, the composite electrocatalysts of Examples 1 to 4 and Comparative Examples 1 to 2 have a current density of 500 mA / cm 2 The overpotential under high current density is shown in Table 3.

[0051] Table 3

[0052] It can be seen from Table 3 that at high current density (500 mA / cm 2 ), the sulfide composite catalyst modified by the noble metal nanoparticles prepared by the present invention has a significantly reduced overpotential, indicating that the composite electrocatalysts of Examples 1 to 4 have excellent electrocatalytic activity in hydrogen evolution by electrolysis of water.

[0053] 5.2 LSV and EIS Test Figure 5 The electrocatalytic performance test results of the catalysts and MoS2 prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown in Figure 1. a is the LSV curve; b is the EIS curve; c is the Ru-MoS2-H2O2 at 500 mA cm -2 a is the stability test curve under the above conditions; d is the LSV curve before and after the stability test. Figure 5 a shows that Ru-MoS2-H2O2 has the best performance in hydrogen production by water electrolysis. Figure 5 b shows that Ru-MoS2-H2O2 has the smallest mass transfer rate and the smallest internal resistance. Figure 5 c for Ru-MoS2-H2O2 at 500 mA cm -2 The stability test under the conditions of 100 ℃ and 200 ℃ showed that the electrocatalyst prepared by the method of the present invention can operate stably for more than 21 hours. Figure 5 d It can be seen that the overpotential of Ru-MoS2-H2O2 increased by only 9.64 mV after the 21-hour stability test, which further shows that the composite electrocatalyst prepared by the present invention has a smaller overpotential and longer stability at a high current density.

[0054] Figure 6 The electrocatalytic performance test results of the composite electrocatalysts and MoS2 prepared in Example 2 and Comparative Example 1 are shown in Figures a, c, e, and g are LSV curves of molybdenum disulfide modified with different precious metal nanoparticles; b, d, f, and h are EIS curves of composite electrocatalysts modified with different precious metal nanoparticles. Figure 6 It can be seen that molybdenum sulfide modified with different precious metal nanoparticles can improve the performance of hydrogen production by water electrolysis, and the optimal hydrogen evolution performance corresponding to the reaction time of different composite catalysts is different.

[0055] Figure 7 The electrocatalytic performance test results of copper sulfide modified with different precious metal nanoparticles in Example 3 are shown in Figure a, where a is the LSV curve and b is the EIS curve. Figure 7 It can be seen that the water electrolysis performance of copper sulfide modified with different precious metal nanoparticles is better than that of the copper sulfide catalyst itself, among which Pd-CuS-H2O2 and Ru-CuS-H2O2 have better performance.

[0056] Figure 8 The electrocatalytic performance test results of iron sulfide modified with different noble metal nanoparticles in Example 4 are shown in Figure a, where a is the LSV curve and b is the EIS curve. Figure 8 It can be seen that the performance of iron sulfide modified with different precious metal nanoparticles is improved in water electrolysis, among which Pd-Fe2S3-H2O2 has better performance.

[0057] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.

[0058] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a composite electrocatalyst, characterized in that: The following steps are involved: mixing a sulfide or selenide with a noble metal solution to obtain a mixture; The mixture is mixed with an oxidant and reacted to obtain the composite electrocatalyst.

2. The method for preparing the composite electrocatalyst according to claim 1, characterized in that: The sulfide or the selenide is in a nanosheet morphology.

3. The method for preparing the composite electrocatalyst according to claim 1, characterized in that: The sulfide is one or more of molybdenum sulfide, cobalt sulfide, nickel sulfide, copper sulfide, and iron sulfide; the selenide is one or more of nickel selenide, indium selenide, and cadmium selenide.

4. The method for preparing the composite electrocatalyst according to claim 1, characterized in that: The amount of the sulfide or the selenide is 1 to 50 mg; The concentration of the noble metal solution is 0.1×10 -4 ~ 0.1 mol / L, the amount added is 1~10 mL; The concentration of the oxidant is 20-30 wt %, and the amount added is 1-200 μL.

5. The method for preparing the composite electrocatalyst according to claim 1, characterized in that: The noble metal is one or more of ruthenium, platinum, rhodium, iridium and palladium.

6. The method for preparing the composite electrocatalyst according to claim 1, characterized in that: The oxidant is one or more of hydrogen peroxide, ozone and sodium hypochlorite.

7. The method for preparing the composite electrocatalyst according to claim 1, characterized in that: The mixture is mixed with the oxidant in a manner of: adding the oxidant at a concentration of 0.1×10 -4 was added to the mixture at a rate of ~0.1 mL / min.

8. The method for preparing the composite electrocatalyst according to claim 1, characterized in that: The reaction temperature is room temperature, and the reaction time is 1 to 20 min.

9. A composite electrocatalyst, characterized in that: The method is prepared according to any one of claims 1 to 8.

10. Use of the composite electrocatalyst as claimed in claim 9 in producing hydrogen by electrolysis of water.

Citation Information

Patent Citations

  • Method for conveniently preparing noble metal monoatomic catalyst

    CN110064410A

  • MoS2 / MoO2 / Ru composite material as well as preparation method and application thereof

    CN111468144A

  • Composite nano material as well as preparation method and application thereof

    CN114772643A

  • MoS2 / MoOx heterogeneous nanosheet as well as preparation method and application thereof

    CN116397238A